2011
DOI: 10.4314/tjpr.v10i1.66539
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Safety Assessment of the Effect of Five Medicinal Plants on Human Peripheral Lymphocytes

Abstract: Purpose: To evaluate, using ethnomedical data approach, five Indian plants used in traditional medicine for cancer and other diseases for their safety and cytotoxic activity on human lymphocytes. Methods: The antiproliferative effect of the 50, 100 and 200 µg/ml aqueous extracts of five plants (leaves of Phyllanthus niruri, Coleus aromaticus, Azadirachta indica and Camellia sinensis, and dried fruit rind of Garcinia indica) were evaluated in vitro using trypan blue dye exclusion and clonogenic assay methods on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…It has also been reported that chemical inhibitors or ACLY RNAi suppress tumor cell growth Bauer et al, 2005). The results showed that Garcinia extracts inhibited lymphocytes and 3T3 fibroblast cell survival because of pronounced cytotoxic effects (Varalakshmi et al, 2011). Selective inhibition of ACLY by Garcinia extract/HCA may help in suppression of tumor cell growth (Migita et al, 2008).…”
Section: Cytotoxic Effectmentioning
confidence: 95%
“…It has also been reported that chemical inhibitors or ACLY RNAi suppress tumor cell growth Bauer et al, 2005). The results showed that Garcinia extracts inhibited lymphocytes and 3T3 fibroblast cell survival because of pronounced cytotoxic effects (Varalakshmi et al, 2011). Selective inhibition of ACLY by Garcinia extract/HCA may help in suppression of tumor cell growth (Migita et al, 2008).…”
Section: Cytotoxic Effectmentioning
confidence: 95%
“…Seaweeds or macroalgae are found to have rich source of secondary metabolites like polysaccharides, sterols, terpenoids, flavonoids, and fatty acids, which acts as excellent drug leads and facilitates the unraveling of novel biosynthetic pathways [ 5 , 6 ]. However, certain metabolites are toxic in nature, which necessitates the toxicological evaluation of natural products, which includes testing of plants for cytotoxic, genotoxic, and mutagenic potentials [ 7 , 8 ]. Mutagenicity is the process of induction of permanent transmissible changes in the genetic material of the cells, whereas genotoxicity is a broader term, which is the ability of a compound to interact with the genetic material and also with other cellular apparatus that maintains the fidelity of the genome [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 Such divergent results may be due to differences in treatment duration, test system, type of extracts and dilution solvent. Therefore, we considered it prudent to evaluate the mechanisms of induced cytotoxicity with regard to mitochondrial membrane potential and mode of cell death by flow cytometry.…”
Section: Ghosh I Et Al: Cyto-genotoxicity Of Hydroxycitric Acid In Vmentioning
confidence: 99%
“…6,7 Paradoxically, recent in vitro studies did not reveal genotoxicity but showed cytotoxicity. 8, 9 Thus, in view of the recent incongruent scientific findings and the rising demand for HCA, the present study was undertaken using multiple cytotoxic (trypan blue dye exclusion (TB) test and MTT assay), genotoxic (comet, DNA diffusion assays) endpoints for the first time, with emphasis on their mechanisms by detection of reactive oxygen species (ROS) generation (to reflect genotoxicity), mitochondrial membrane potential (signified by ΔΨm) and apoptosis/ necrosis (to reflect cytotoxicity) in human lymphocytes. The hemolytic effect of HCA in erythrocytes was also assessed.…”
Section: Introductionmentioning
confidence: 99%